Do conhecimento da alma à alma do conhecimento - Patrícia Lucchesi Barbosa (2014)
This thesis proposes to demonstrate the deep connection there is between the notion of soul, such as it is presented in Plato´s Republic and that of science, in the Theaetetus, bringing forward the importance of Plato´s anthropology as well as of his epistemology for a more comprehensive understanding of his philosophy. We consider, anachronistically, since these two disciplines are not separated in Greek thought, that the link between them is a political interface, which, on its turn, is intrinsically related to his ethics. With the aim of demonstrating how knowledge, in general, and philosophy, in particular, are connected to the upbringing of a citizen towards a better life in the city, we analyze the philosopher´s profile, as opposed to that of the tyrant´s, and emphasize the fact that the practice of philosophy is sustained by Plato as a necessary pleasure and a very special kind of prophylaxis for the just city. Thus, Plato´s text reflects both a historical and a theoretical complexity which cannot be equated with a mere speculative or utopian project. Politics is inseparable from ethics, since what is searched is the ordering of individual soul in its internal differentiation as well as that of the functional groups in the unity of the city. Ethics, on its turn, cannot do away with knowledge, which is built by a philosophical educational project that involves the soul as a whole. Thus, this complex network constitutes a constructive philosophy, whose aspiration is to make human beings wiser and better, not only better informed experts.